OBJECTIVE STRUCTURED PRACTICAL EXAMINATION (OSPE), AS A TOOL FOR THE ASSESSMENT OF PRACTICAL SKILLS OF UNDERGRADUATE M.B.B.S STUDENTS - Farkhanda Jabeen; Sadaf Zia; Sumera Riaz (Journal of University Medical & Dental College, 2016)
ABSTRACT INTRODUCTION: Skills based learning is a part and parcel of medical education. OSPE is a tool used widely in the assessment of medical students’ practical skills. This study is designed to analyze the response of medical students’ on OSPE. This is a small effort to evaluate the feasibility of using OSPE as an assessment tool in undergraduate medical students. MATERIALS AND METHODS: A close ended questionnaire was distributed to 50 second year MBBS students to assess students’ evaluation of the OSPE. RESULTS: According to this study OSPE has been accepted as a fair mode of assessment by 66% of students and 60% of them declared it a reliable and effective tool. Almost 78% students were stress free during OSPE as compared to viva and 94% felt the need of more time requirement at each station. About 88% students felt that this format helps them to identify their weak areas and 80% gained confidence over the subject. To summarize, students declared OSPE an effective and useful tool of assessment and gave us a constructive feedback which will be helpful for further improvement and standardization in future. CONCLUSION: Use of OSPE is reliable and feasible for formative as well as summative assessment in the undergraduate medical students.